Implementation of Quick UDP Internet Connections (International Journal of Engineering and Computer Science, 2020)
With the advent of the Internet growth worldwide, we need to have a protocol which is faster and provides a better support for the following problems:• Faster Connection Establishment Time• Good Congestion Control• Connection Migration• Good Error CorrectionOne of the key aspects taken under consideration was current scenario of connection establishment time whenever a website is requested and poor video buffering over existing Internet Connections.The prime objective is to create a proxy server which routes the incoming connection requests to QUIC supported libraries if the client supports QUIC. If the client does not support QUIC then it routes the incoming request to existing web server which can then handle the request using TCP.  After creation of the proxy server a website has to be created using which we can test various aspects of the QUIC protocol.Keyword: Quick, Protocol, UDP, Network